Statistical Analysis of the Formative Experiment on Detection of Prerequisites of Internet Technologies Usage in the Learning Process and Determination of the Level of Future Philologists’ Motivation to Studying Foreign Languages with the Help of Internet - Serhii Danylyuk (Pedagogical Discourse, 2013)
The article deals with the statistical analysis of the results of the formative experiment on detection of prerequisites of usage by students of Internet technologies in the educational process, as well as with determination of the level of motivation of students to study foreign languages with the help of Internet technologies. The paper also deals with the selection of complex diagnostic procedures to identify the conditions for usage of Internet technologies in the educational process and to determine the level of motivation to study foreign languages with the help of Internet technologies. In addition, the procedure of conducting of the investigation with the help of the selected diagnostic procedures is described in the paper.